SISTEM PERINGATAN DINI KETAHANAN PANGAN DAERAH: PENATALAKSANAAN DAN PELIBATAN SELURUH PEMANGKU KEPENTINGAN - Lukman Hakim (Universitas Negeri Medan, 2014)
Early Warning System (EWS) is a solution of food security of the most important in the management of the policy (Governance) food security. This study departs from best practices (best practices) in the regional autonomy that has been applied in the area surrounding the Surakarta and management of food security that is initiated by Bank Indonesia (BI) and the Central Statistics Agency (BPS) through Regional Inflation Control Team (TPID). This study uses FGD and AHP method are used to build the index of food security EWS. The results of this study indicate that areas that do not have high production in food commodities indeed have a higher susceptibility than having high production.